Nepali Army in Climate-Induced Security Challenges - Baniya, Dharma Bahadur (Unity Journal, 2024)
In the interconnected world today, the connection between climate change, peace, and security has gained significant recognition. Security actors, including the armed forces, are increasingly confronted with extreme weather events demanding for assistance both at home and abroad. Their military assets and ability to operate are affected by changing weather patterns, rising sea levels, and other climate impacts. Climate change is transforming the way we think about security. As climate change intensifies, its impacts risk exacerbating existing social, economic, and environmental drivers of insecurity at local levels (where communities struggle to cope with converging pressures) and globally (when resources and ecosystems are shared across national borders). Climate insecurity hinders the adaptation efforts, and risks leaving already vulnerable communities even poorer and less resilient to interlinked climate and security crises. As the global temperature is rising, climate and disaster risks in Nepal are affecting people, the environment, the economy, development gains, and overall security of the country. This article begins by briefly highlighting the climate-induced insecurity to Nepal and efforts made to minimize its impacts. Then the article endeavors to present a comparative overview of the leading greenhouse gas (GHG) emitting nations including Nepal followed by the analytical examination of climate change impacts on states and armed forces. Finally, the article concludes by presenting suitable recommendations to the NA in responding the climate-induced security challenges. The article is subjectively prepared by analytically reviewing various literatures on climate-induced security challenges in the world today.